CHALLENGES AND OPPORTUMITIES FOR RURAL WOMEN ENTREPRENUERS OF TUMAKURU DISTRICT – A SOCIOLOGICAL STUDY - N, Vijayalakshmi.; A. M, Narayanaswamy. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Women entrepreneurship is gaining importance in India in the wake of globalization and economic liberalization. Women entrepreneurs tend to be highly motivated, self-disciplined & self-directed. Women’s entrepreneurship is important for women’s position in society, and economic development of women will lead to development of family, community and country. It opens up new avenues for creating employment opportunities for women and men. The present paper focuses on parameters to be focused to enhance the entrepreneurial skill of rural women and in turn their empowerment. Rural women’s economic and social development is necessary for overall economic development of society and nation. Rural women are now increasingly run their own business yet their entrepreneurial potential, managerial skill and socio-economic contribution remain largely neglected. Women entrepreneurship development is the instrument of women empowerment. Empowerment through entrepreneurship leads to self-fulfillment and makes women aware about their status, existence, right and their position is in the society. In modern era, women are becoming socially empowered, and economically empowered through business ownership. On the other hand, empowerment of rural women is also very significant. Economic empowerment of rural women will lead to the development of our country and it is very necessary to give keen attention over the empowerment of women in the rural areas for the real development of our country in all spheres.